Evaluation of nutritional status in older persons: nutritional screening and assessment - Bauer, Jürgen; Kaiser, Matthias; Sieber, Cornel (Current Opinion in Clinical Nutrition and Metabolic Care, 2010)
Purpose of reviewMalnutrition is highly prevalent in the older population. It is associated with declining functionality and relevant health deficits. This review presents the principles of successful nutritional screening and assessment in older persons.Recent findingsAlthough no gold standard for the diagnosis of malnutrition can serve as reference, a large number of nutritional screening tools have been developed during the past two decades. For efficient screening, the most appropriate tool has to be selected based on setting and practicability. The screening intervals have to be chosen according to the population screened. Although screening has to be performed routinely and systematically in a very practical and efficient manner, nutritional assessment has to be individualized to provide information on the grade of malnutrition and its cause. The development of a local guideline that reflects local expertise and resources will prove essential for successful nutritional management.ConclusionNutritional screening and assessment should be a standard of care for older persons. It has to be considered as a clearly defined two-step procedure, which has to reflect setting and local resources. Further adaptations of the available screening tools with regard to ethnic characteristics are indicated.
Keywords: elderly; malnutrition; nutritional assessment; nutritional screening; screening tools